George MacDonald : a biography of Scotland's beloved storyteller - Phillips, Michael R., 1946- (Minneapolis, Minn. : Bethany House, 2005)
"A revealing look into the life, spiritual journey, and writings of the popular yet controversial 19th-century novelist, George MacDonald. Michael Phillips unveils the life and times of his literary mentor in this portrait of a great writer of faith, set in the Scottish land he loved"--Provided by publisher.
Originally published: c1987.
Includes bibliographical references (p. [366]-374) and index.
Keywords: MacDonald, George, -- 1824-1905.; Fantasy fiction, Scottish -- History and criticism; Authors, Scottish -- 19th century -- Biography; Christian fiction -- History and criticism; Scotland -- In literature